(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2015)
International human rights law relies on state sovereignty to localize suggested policy with codification and enforcement in an attempt to reconcile universalism with particularity. However, amidst domestic governance developments from post-conflict state building and self-determination, governmental instability complicates and often overlooks priorities of international human rights for more tangible domestic infrastructure, such as basic human needs rather than seemingly suggested rights ideals. This does not diminish the significance of human rights, though, pertaining to the rights of the child in addressing gender-based violence through the elimination of female genital mutilation, for example. While state-centric localization is currently prioritized for implementing international law, the rule of law is more integrated throughout the realms of societal structure, culture, and institutions in addition to the legal realm. If the legal realm is disrupted with instability, violence, and discontinuity, how does society internalize and integrate international human rights law over time, and can it be sustainable despite instability? This research evaluates the development of the rule of law, and its effectiveness, regarding female genital mutilation (FGM) as a case study in Iraqi Kurdistan from the end of the Iran-Iraq War in 1988 until 2013, the early years of the Kurdistan Regional Government’s parliament. Comprehensive rule of law evolution can be measured through comparing domestic legal developments through state-centric policy and enforcement, or lack thereof, with cultural internalization and non-governmental engagements. By studying the legal and cultural realms’ interaction with the anti-FGM discourse over Iraqi Kurdistan’s past two decades, this research will determine the role of a continuous society overlaid by intermittent legal structures in the sustainability of negotiating cultural relativity with universal human rights.